Strengthening and repair of one-way and two-way self-compacted concrete slabs using near-surface-mounted carbon-fiber-reinforced polymers. Issue 11 (August 2019) - Ashteyat, Ahmed M; Al Rjoub, Yousef S; Obaidat, Ala' T.; Dagamseh, Huthaifah
The effectiveness of near-surface-mounted carbon-fiber-reinforced polymers on strengthening and repair of self-compacted concrete slabs was investigated experimentally and numerically. Twenty slabs were cast (10 one-way and 10 two-way) and tested under four-point load. Strengthening and repair effectiveness was investigated on slabs using near-surface-mounted carbon-fiber-reinforced polymer strips with straight and inclined orientation. Repair was performed on eight slabs using near-surface-mounted carbon-fiber-reinforced polymer strips with an orientation based on the best cost/capacity ratio, with two preloading levels: 35% and 50% of the ultimate load of the control slab. The results showed that using near-surface-mounted carbon-fiber-reinforced polymers increases the ultimate strength of one-way strengthened self-compacted concrete slabs (45%–163%) for both strip orientation, with the straight orientation performing better. Also, the cracking load and stiffness increased, while deflection decreased. The increase in ultimate strength for strengthened two-way slabs was 15% to 17%. The ultimate deflection and toughness of the two-way strengthened slabs increased 43% and 34%, respectively. Using near-surface-mounted carbon-fiber-reinforced polymers restored the load capacity of repaired one-way and two-way slabs but was more effective for one-way slabs. The repaired one-way slabs regained up to 223% of the control slabs' ultimate strength, with a significant increase in stiffness (296%). The repaired two-way slabs regained up to 116% of the control slabs' ultimate strength. The strength was higher in the case of the 50% preload compared to 35% preload. The finite element model shows somehow a reasonable capability of predicting the experimental behavior with a gap in terms of the stiffness and the maximum load.